Design and Analysis of a Fibre-Shaped Micro-Actuator for Robotic Gripping. (1st March 2013) - Borboni, Alberto; Aggogeri, Francesco; Faglia, Rodolfo
A prototype of an automatic micropositioning system was developed. This prototype uses a shape memory alloy (SMA) actuator, a dedicated PI controller and a piece of software to command a desired motion profile for the actuator. The proposed micropositioning system is characterized by a 4 mm stroke, a 1 μm resolution and a 70 g nominal force and can be commanded directly from a personal computer and without human retroaction. The closed loop positioning resolution (1 μm) is obtained in spite of inaccurate system behaviour during its movement.